12x - 8y = -12
6x + 4y = -30
Multiply the 2nd equation by 2, to make the Y coefficients opposite:
6x + 4y = -30 x 2 = 12x + 8y = -60
Now add the two equations:
12x -8y = -12 + 12x +8y = -60
= 24x = -72
Divide bothe sides by 24 to solve for x:
x = -72/24
x = -3
Now replace x with -3 in the first equation to solve for y:
12(-3) - 8y = -12
-36 - 8y = -12
Add 36 to each side:
-8y = 24
Divide both sides by -8 to solve for y:
y = 24 / -8
y = -3
X = -3 and y = -3
(-3,-3)
Answer:
D α H
k = D/H
k = 3.50
Step-by-step explanation:
Amount paid, D is directly proportional to the number of hotdogs, H
D = $3.50 per hot dog
D = $3.50 is directly proportional to 1 hotdog
Hence,
D α H
D = kH
k = proportionality constant
H = 1
3.50 = k
k = 3.50
k = D/H
Answer:
-1.32-34.7= -36.02
Step-by-step explanation:
A negative minus a negative will always give you another negative.
So, to do this quickly just see this equation "-1.32-34.7" as this equation "1.32+34.7" and add a negative once you've finished.
1.32+34.7= 36.02
Now add the negative.
-36.02
Answer:
x = 6
y = -4
Step-by-step explanation:
Plug y into the first equation.
5x - 7(-x+2) = 58
Then, solve for x.
Plug in x back to any one of the equations to find y.
Answer:20
Step-by-step explanation:
8 is the number of edges so 8 mutiplyed by 2.5= 20